LEXICAL AND SEMANTIC NORMS IN FORMATION OF STATE OFFICIAL LANGUAGE COMPETENCY - Liliia V. Kharchuk (Вісник університету ім. А. Нобеля. Серія Філологічні науки, 2021)
The new stage of Ukrainian literary language development began in the late 20th century, because state-making processes had legitimated the status of the Ukrainian language due to the law, following the main goal – to facilitate self-expression of the national genotype, raising prestige and full-fledged functioning of the state language in independent Ukraine. Since the reality is formed on the basis of personal activity, one of the leading tasks is upbringing the need of every speaker to use the state language fluently as the means for communication, as the means of forming intellectual culture, national self-awareness, which thus has direct impact on mentality and moral qualities of a person. The situation concerning the languages in the communicative environment of Ukraine obliges all speakers to accept the issues of the language and the speaking in a systematic and complex way. Command of a normative native language is the assignment for every aware citizen, who is obliged to know how to use the entire lexical heritage. A language is a weighty part of professional competency, a sensitive indicator of general culture, that is why every speaker should care about the high culture of their language. Perfect usage of a language becomes an important component of training experts in any field, particularly in the field of state governing, since the use of a language promotes their self-expression. Official activity definitely requires not only professionalism, but also thorough language competency. Our research is actual because we constantly need to work on the problems of language culture in the field of state governing, since, as a social phenomenon, the Ukrainian language reflects precise historical peculiarities, typical to a certain social and historical period: the development of new word constructions, the emergence of new words, a number of borrowings from other languages, etc. The purpose of our investigation is to find out and analyze the violations of lexical and semantic norms in official and business communication of state officials, to justify the ways and means to correct the violations of the lexical and semantic norm. Reaching the set purpose meant carrying out the following tasks: to analyze the official and business language of state officials; to single out the most spread lexical and semantic mistakes and downsides in speaking, to give recommendations on eliminating mistakes in order to improve the speaking culture of state officials in the field of their professional activity. In the investigation, there is applied a wide range of contemporary methods and approaches of research: language facts are considered from the position of the functional approach; by means of the methods of the generalization and classification analysis the types of mistakes met in the language of state officials were singled out; the comparing and contrasting analysis has allowed to find out the facts of interfering influence of the Russian language on Ukrainian, to single out the types of the interference consequences at the lexical and semantic level. In the proposed research, there is the analysis of the official and business language of state officials, different consequences of interferencial interaction of closely native languages (Ukrainian and Russian) are realised and typified by comparing the language of state officials to the current norms of the modern Ukrainian literary language. The most spread lexical mistakes and downsides are found to refer to: not motivated usage of words which results in “surgick”; usage of so-called words-parasites with no need; usage of the words which are inappropriate from the point of view of the literary norm and the etiquette rules; abuse of the words derived from foreign languages, especially from English; irrelevant tautology in oral speech, redundancy of words ( pleonasm ); confusing paronyms. Due to the analyzed language material there are linguistic explanations and recommendations on the ways and means of preventing, correcting and eliminating realised mistakes in the language of state officials. It is proved that state governors are obliged to obey communicative features of language culture, namely: its correctness, accuracy, logic, purity, pithiness and relevance.